PENGARUH KONVERGENSI IFRS TERHADAP PERSISTENSI LABA: STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2015 - Vania Adi; Yie Ke Feliana (Akuntansi dan Teknologi Informasi, 2018)
This research aims to test whether the more convergent IFRS in Indonesia can make company’s earning more persistence or not, also this research aim to test can the operating income this year can predict the net income in next year more rather than non-operating income. This research uses quantitative approach with multiple regression analysis. Researcher use companies listed in Indonesia Stock Exchange within 2012 – 2015 period as the sample. There are 304 companies used in this research. The results show that the more convergent IFRS in Indonesia can make company’s earning more persistence even the coefficient value fluctuates, so the net income in current year can be used to predict the net income in next year. Meanwhile, operating income proved can predict net income in next yearrather than non-operating income even the ability to predict was decreased in 2015.